Module 5: Teaching for Thinking - Wan Yusoff, Wan Mazwati (2021)
This module provides exposure and explication on the most important skills that human should have, which is thinking skills, and how to teach for thinking. The ability to think, provide and make choices distinguish human from other species and because of this human is given the responsibility to govern the earth; and because of thinking ability also human is made responsible for their actions.